Aza-Michael Mono-addition Using Acidic Alumina under Solventless Conditions - Giovanna Bosica; Roderick Abdilla (Molecules, 2016)
Aza-Michael reactions between primary aliphatic and aromatic amines and various Michael acceptors have been performed under environmentally-friendly solventless conditions using acidic alumina as a heterogeneous catalyst to selectively obtain the corresponding mono-adducts in high yields. Ethyl acrylate was the main acceptor used, although others such as acrylonitrile, methyl acrylate and acrylamide were also utilized successfully. Bi-functional amines also gave the mono-adducts in good to excellent yields. Such compounds can serve as intermediates for the synthesis of anti-cancer and antibiotic drugs.